Pengaruh Breathing Exercise Diafragma (Bed) Terhadap Penurunan Nyeri Pada Pasien Post Sectio Caesarea Dengan Spinal Anestesi Di Rumah Sakit Umum Daerah Tgk Chik Ditiro Sigli - Said Muhammad Yusuf; Murniati Murniati; Feti Kumala Dewi (Universitas Harapan Bangsa Purwokerto, 2023)
Non-pharmacological therapy that can be done to reduce pain in post sectio caesarea patients can be done with diaphragmatic breathing exercise. This study aims to determine the effect of diaphragmatic breathing exercise on reducing pain in post sectio caesarea patients with spinal anesthesia at Tgk Chik Ditiro Sigli Hospital. This research method is a Quasi Experiment with a pretest – posttest approach with a control group. The number of samples in this study were 40 sectio caesarea patients who were divided into 2 groups, namely 20 experimental groups and 20 control groups. The instrument used in this study to measure the pain scale is the Phase Pain Scale (FPS). The collected data were analyzed univariately and bivariately using the Wilcoxon Test. The results showed that the average pain scale in the intervention group before being given the diaphragmatic breathing exercise technique was 5 (SD 1.29777 and confidence interval (2-6)) and after being given the diaphragmatic breathing exercise technique the average pain scale decreased to 3. 1 (SD 1.11921 and confidence interval (1-5)). There is an effect of diaphragmatic breathing exercise on pain reduction in post-cesarean section patients with spinal anesthesia with a p-value of 0.0001 (P<0.05). This study concluded that there was an effect of diaphragmatic breathing exercise on pain reduction in post-cesarean section patients with spinal anesthesia at Tgk Chik Ditiro Sigli Hospital.